Karl Polanyi and the Contemporary Political Crisis: Transforming Market Society in the Era of Climate Change - Kirby, Peadar (Bloomsbury Publishing, 2020)
Has politics reached breaking point? Rather than defending liberalism or abandoning it, how can a socially just and ecological alternative be built? Peadar Kirby investigates the causes of our current multifaceted global crisis by drawing on the work of Karl Polanyi. This book explores Polanyi's theory that social disruptions result from the attempt to run society according to the rules of the market. Drawing on these ideas, it outlines pathways towards an alternative future that overcome weaknesses in Marxism. Linking the ecological, political and socio-economic crises, Kirby identifies that an alternative socio-ecological model is emerging, consistent with the insights of Polanyi. Karl Polanyi and the Contemporary Political Crisis is an urgent intervention into key debates on the future of politics, on the low-carbon transition, on automation and on the emerging world order.
Keywords: climate change; ecological crisis

Karl Polanyi and Twenty-first-century Capitalism - Desai, Radhika; Levitt, Kari Polanyi (Manchester University Press, 2020)
As far right movements, social disintegration and international conflict emerge from the decay of the neoliberal order, Karl Polanyi's warnings against the unbridled domination of markets, is ever more relevant. The essays in Karl Polanyi for the 21st Century extend the boundaries of our understanding of Polanyi's life and work. They will interest Polanyi scholars and all interested in socialism and our future after neoliberalism. One asks whether, following Keynes and Hayek, Polanyi's ideas will shape the twenty-first century. Some clarify, for the meaning of money as a fictitious commodity. Others resolve difficulties in understanding the building blocks of Polanyi's thought: fictitious commodities, the double movement, the United States' exceptional development, the reality of society, and socialism as freedom in a complex society. And yes others explore how Polanyi sheds light on income inequality, world systems theory, comparative political economy.
Keywords: capitalism; double movement; neoliberalism; reality of society; socialism

Karl Polanyi - The Life and Works of an Epochal Thinker - Thurnher, Armin; Aulenbacher, Brigitte; Novy, Andreas; Marterbauer, Markus; Polanyi Levitt, Kari (2020)
On 8 May 2018, the International Karl Polanyi Society was founded in Vienna. This marked the beginning of a new phase of engagement with a thinker who had already come to be regarded as a centennial figure in the Anglo-Saxon world. This book serves as an introduction to The Great Transformation, Polanyi’s magnum opus and one of the most important works of the 20th century. It helps us to understand the background to Karl Polanyi’s intellectual career, sketches the lives of his family members, describes the milieus of Budapest, Vienna, London and New York, which were such informative influences in his life, and sheds light on his relationship with contemporaries such as Keynes, Mises and Hayek. Renowned Polanyi researchers, including, most notably his daughter Kari Polanyi Levitt, elucidate Polanyian concepts such as ‘fictitious commodities’ and apply his analysis to an era when everything seems to be subjected to the mechanics of the market.
Sociology
Keywords: Great Transformation; The (Book); fictitious commodities